The Local Wisdom of Sambas Malay Ethnic Assessed from Character Mathematical Connections - Bistari Bistari (STKIP Singkawang, 2017)
The local wisdom of the Sambas Malay ethnic from generation to generation in this study are 12 species. Among the 12 are two local wisdom that is almost extinct ie behind the mat and ngukor. This study aims to obtain information and describe related local wisdom ethnic Malay Sambas studied in mathematical connection. The method used in this research is descriptive qualitative. Data obtained through questionnaires and interviews on the parties concerned. The result of the research shows that there are 12 local wisdom of Melayu Sambas ethnic that ever exist in social life, and that is still realized 10 local wisdom (except ngukor and pacoan). While the local wisdom of Malay Sambas ethnic who have relevance to the mathematical connection and strengthening the education of social and environmental care characters there are 10 kinds. To categorize and pacoan pertained weak connection relevance.